2010
DOI: 10.1007/dcr.0b013e3181d972a9
|View full text |Cite
|
Sign up to set email alerts
|

Tract Length Predicts Successful Closure With Anal Fistula Plug in Cryptoglandular Fistulas

Abstract: Anal fistula plug repair of cryptoglandular anorectal fistulas is more successful for long-tract fistulas. Although the overall success is modest, limiting surgical indications to fistulas exceeding 4 cm may maximize benefits of the plug technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
3
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 23 publications
0
51
3
5
Order By: Relevance
“…In our series, there were 14 (56%) tracts in males and 11 (44%) tracts in females. In contrast to results reported by others [18], more tracts healed in men than in women, supporting the literature that suggests that complex tracts, such as anterior fistula tracts in women, are notoriously difficult to heal [19]. Clearly, the disparate results published in the literature on the efficacy of the AFP may need to take gender, as well as tract length, into consideration when predicting best outcomes and choosing the ideal patient for the placement of the plug.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In our series, there were 14 (56%) tracts in males and 11 (44%) tracts in females. In contrast to results reported by others [18], more tracts healed in men than in women, supporting the literature that suggests that complex tracts, such as anterior fistula tracts in women, are notoriously difficult to heal [19]. Clearly, the disparate results published in the literature on the efficacy of the AFP may need to take gender, as well as tract length, into consideration when predicting best outcomes and choosing the ideal patient for the placement of the plug.…”
Section: Discussioncontrasting
confidence: 56%
“…A recent study reported that tract length predicts the outcome of AFP placement [18]. In that report, tracts that were 4cm in length or longer were 3 times more likely to heal than tracts that were less than 4cm in length (61% vs. 21%).…”
Section: Discussionmentioning
confidence: 97%
“…The plug may however be useful in Crohn's fistulas, where it may be considered as an alternative treatment, although the success rate even in these cases is low [8][9][10][11]. Some studies have shown that longer tracts have better chances of closure [12]. Results with bioprosthetic plugs have shown higher results varying from 54 % to 72 %, although the test series have been very small [13][14][15].…”
Section: Which Is the Best Surgery For Fistula In Ano?mentioning
confidence: 99%
“…Grundlagen und Indikationen des Analfistelplugs wurden 2007 in einem Konsensuspapier publiziert [58]. Die veröffentli-chen Literaturergebnisse bilden überwie-gend Beobachtungsstudien ab ( [8,39,47,48,51,79,82,94,132,153,156,175,196,197,229,240,241,257,269,282,283,295,322]; . Tab.…”
Section: Analfistelplugunclassified